149k views
13 votes
Please help me solve and show all steps, thank you!!!

Please help me solve and show all steps, thank you!!!-example-1

1 Answer

5 votes

Answer:

y = -2x² + 12x - 14

Explanation:

Isolate the "-2" in (x - 3)² by using brackets:

  • ⇒ y = -2(x - 3)² + 4
  • ⇒ y = -2[(x - 3)²] + 4

Using the formula (a - b)² = a² - 2ab + b²:

  • ⇒ y = -2[(x - 3)²] + 4
  • ⇒ y = -2[x² - 2(x)(3) + 3²] + 4

Open the brackets on the R.H.S

  • ⇒ y = -2[x² - 6(x) + 9] + 4
  • ⇒ y = -2x² + 12(x) - 18 + 4

Simplify the expression on the R.H.S

  • ⇒ y = -2x² + 12(x) - 18 + 4
  • y = -2x² + 12x - 14
User Shivam Verma
by
5.3k points